KEARIFAN LOKAL DAN PEMBENTUKAN KARAKTER SISWA DALAM PROGRAM P5 DI POLEWALI MANDAR - Dyan Paramitha Darmayanti; Manda, Darman; Arifin, Iqbal (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study evaluates the effect of the local wisdom-based Pancasila Student Profile (P5) Strengthening Programme on student character building in Polewali Mandar District, as well as how community and parental involvement supports learning quality. This study used a qualitative method with a descriptive approach, involving five teachers, five students and five parents from four primary schools. All informants used pseudonyms to keep their identities confidential. Data were collected through in-depth interviews, direct observation, and documentation. The results showed that the integration of local wisdom values such as gotong royong (siwaliparri), mutual respect (metawe), as well as traditions such as Paduppa Dance, Kue Jepa, and Kue Kateri Sala‘ had a positive impact on students’ character building. Students become more disciplined, care about the environment, work better together, and understand local cultural values. The active involvement of parents and communities in local wisdom-based activities strengthens students' motivation, creating a more relevant and supportive learning environment. This research emphasises the important role of the community and family in ensuring the success of the P5 programme in shaping students' strong and responsible characters.